A new Arthula Cameron (Ichneumonidae, Cryptinae) parasitoid of Ropalidia plebeiana Richards (Vespidae) and host of Amoturoides breviscapus Girault (Torymidae) (Hymenoptera) - Ubaidillah, Rosichon; Yamaguchi, Goshi; Kojima, Jun-Ichi (Zootaxa, 2009)
Arthula plebeja Ubaidillah and Kojima, sp. nov., a parasitoid of the Australian paper wasp Ropalidia plebeiana Richards, and host of the torymid hyperparasitoid Amoturoides breviscapus Girault, is described and illustrated. Both A. plebeja and A. breviscapus are estimated to have a bivoltine life cycle, the first overwintering in the pupal stage, and the second in the prepupal and/or pupal stage.